Heat shock protein 70 inhibitors suppress androgen receptor expression in LNCaP95 prostate cancer cells. Issue 9 (12th August 2017) - Kita, Kazuaki; Shiota, Masayuki; Tanaka, Masako; Otsuka, Asuka; Matsumoto, Masaki; Kato, Minoru; Tamada, Satoshi; Iwao, Hiroshi; Miura, Katsuyuki; Nakatani, Tatsuya; Tomita, Shuhei
Abstract : Androgen deprivation therapy is initially effective for treating patients with advanced prostate cancer; however, the prostate cancer gradually becomes resistant to androgen deprivation therapy, which is termed castration‐resistant prostate cancer (CRPC). Androgen receptor splice variant 7 (AR‐V7), one of the causes of CRPC, is correlated with resistance to a new‐generation AR antagonist (enzalutamide) and poor prognosis. Heat shock protein 70 (Hsp70) inhibitor is known to decrease the levels of full‐length AR (AR‐FL), but little is known about its effects against CRPC cells expressing AR‐V7. In this study, we investigated the effect of the Hsp70 inhibitors quercetin and VER155008 in the prostate cancer cell line LNCaP95 that expresses AR‐V7, and explored the mechanism by which Hsp70 regulates AR‐FL and AR‐V7 expression. Quercetin and VER155008 decreased cell proliferation, increased the proportion of apoptotic cells, and decreased the protein levels of AR‐FL and AR‐V7. Furthermore, VER155008 decreased AR‐FL and AR‐V7 mRNA levels. Immunoprecipitation with Hsp70 antibody and mass spectrometry identified Y‐box binding protein 1 (YB‐1) as one of the molecules regulating AR‐FL and AR‐V7 at the transcription level through interaction with Hsp70. VER155008 decreased the phosphorylation of YB‐1 and its localization in the nucleus, indicating that the involvement of Hsp70 in AR regulation might be mediated through the activation and nuclear translocation of YB‐1. Collectively, these results suggest that Hsp70 inhibitors have potential anti‐tumor activity against CRPC by decreasing AR‐FL and AR‐V7 expression through YB‐1 suppression. Abstract : In this study, we show that heat shock protein 70 (Hsp70) inhibitors regulate androgen receptors, including the full‐length AR (AR‐FL) and the splice variant AR‐V7 that is a major cause of castration‐resistant prostate cancer (CRPC). Treatment of Hsp70 inhibitors reduced viability, increased apoptosis, and decreased the protein levels of both ARs in LNCaP95 cells, an androgen deprivation‐resistant prostate cancer cell line. We further demonstrate that these effects are mediated by interactions with the transcription factor Y‐box‐binding protein 1.